2018
DOI: 10.3390/ijerph15030433
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Variation in General Practice: A Survey among General Practitioners in Denmark

Abstract: Background: Previous studies have demonstrated that high levels of physician empathy may be correlated with improved patient health outcomes and high physician job satisfaction. Knowledge about variation in empathy and related general practitioner (GP) characteristics may allow for a more informed approach to improve empathy among GPs. Objective: Our objective is to measure and analyze variation in physician empathy and its association with GP demographic, professional, and job satisfaction characteristics. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 68 publications
1
27
2
2
Order By: Relevance
“…The study results showed no significant differences based on gender or HCP training. This contrasts with some previous studies which have identified gender ( Toussaint and Webb, 2005 ) and HCP status ( Charles et al, 2018 ) as mediators of empathy. The study also explored in more detail the training’s impact on individual’s perception of role and engagement.…”
Section: Discussioncontrasting
confidence: 99%
“…The study results showed no significant differences based on gender or HCP training. This contrasts with some previous studies which have identified gender ( Toussaint and Webb, 2005 ) and HCP status ( Charles et al, 2018 ) as mediators of empathy. The study also explored in more detail the training’s impact on individual’s perception of role and engagement.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several hypotheses that could explain why the mean duration of follow-up was relatively short and the proportion of participants followed for more than five years relatively low in general practices in Germany. For example, a recent study including 464 Danish GPs reported substantial variation in empathy between physicians, and this variation was significantly associated with several factors, such as the physician-patient relationship and physicians' interactions with their colleagues (11). Since the diagnosis of BC has major psychological effects (16), women with BC may be more likely than women with other chronic conditions (e.g., osteoporosis, hypertension, diabetes) to change doctors when they identify a lack of empathy in their physician.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little is known about the duration of follow-up in BC patients in GP practices after the diagnosis of cancer, and it is possible that BC survivors change doctors more frequently than people with other conditions (e.g., osteoporosis, diabetes, hypertension). This may be due to several reasons, such as the primary care physician's lack of experience with cancer or his/her lack of empathy (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…e research instrument was designed following an extensive literature review on the topic of motivation, job satisfaction and professional performance(Babic, Kordic and Babic, 2014;Charles, et al, 2018;Lambrou, Kontodimopoulos and Niakas, 2010;Maslow, 1943;Mutale et al, 2013;Porter, 1961), as well as own previous research (Ștefan, Popa and Dobrin, 2016).  e proposed conceptual model was operationalized by seven latent constructs, each of them measured by several observed variables. e fi ve dimensions of motivation, inspired by Maslow's hierarchy of needs were assessed by 15 items (Babic, Kordic and Babic, 2014; Burduș and Popa, 2016; Lambrou, Kontodimopoulos and Niakas, 2010;Maslow, 1943;Porter, 1961), asking the respondents how motivated they are in their professional activity by: ( 1) salary, other material benefi ts and work schedule -corresponding to the physiological needs dimension; (2) working conditions, organization staff policy, workplace safety and health and pension insurance -corresponding to the safety dimension; (3) relations with colleagues and teamwork -corresponding to the love and belonging dimension; (4) possibility to assume responsibilities, performance recognition by colleagues and performance recognition by superiors -corresponding to the esteem dimension, and (5) possibilities to value skills, the possibilities to always learn new things and career development possibilities -corresponding to self-actualization.…”
mentioning
confidence: 99%
“… e proposed conceptual model was operationalized by seven latent constructs, each of them measured by several observed variables. e fi ve dimensions of motivation, inspired by Maslow's hierarchy of needs were assessed by 15 items (Babic, Kordic and Babic, 2014; Burduș and Popa, 2016; Lambrou, Kontodimopoulos and Niakas, 2010;Maslow, 1943;Porter, 1961), asking the respondents how motivated they are in their professional activity by: ( 1) salary, other material benefi ts and work schedule -corresponding to the physiological needs dimension; (2) working conditions, organization staff policy, workplace safety and health and pension insurance -corresponding to the safety dimension; (3) relations with colleagues and teamwork -corresponding to the love and belonging dimension; (4) possibility to assume responsibilities, performance recognition by colleagues and performance recognition by superiors -corresponding to the esteem dimension, and (5) possibilities to value skills, the possibilities to always learn new things and career development possibilities -corresponding to self-actualization. A 5-point Likert scale, ranging from 1 (not at all) to 5 (to a very large extent) was used for measurement.Job satisfaction was measured by only one question, asking the respondents (on a 5-point Likert scale, where 1 = not at all and 5 = to a very large extent), how satisfi ed they are with their present professional activity( Charles et al, 2018;Lambrou, Kontodimopoulos and Niakas, 2010;Mutale et al, 2013).…”
mentioning
confidence: 99%